2020
DOI: 10.3390/catal10040427
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Melia azedarach and Ricinus communis Oil by Transesterification Process

Abstract: Biodiesel is a renewable fuel usually produced from vegetable oils and animal fats. This study investigates the extraction of oil and its conversion into biodiesel by base-catalyzed transesterification. Firstly, the effect of various solvents (methanol, n-hexane, chloroform, di-ethyl ether) on extraction of oil from non-edible crops, such as R. communis and M. azedarach, were examined. It was observed that a higher concentration of oil was obtained from R. communis (43.6%) as compared to M. azedarach (35.6%) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…59) and the seed oils were reported to possess an excellent energy substitute properties. The physicochemical results of the biodiesel showed that it can be used in any diesel engine (53). Many studies on the production of biodiesel from vegetable and seed oils were presented (5, 16, 43, 60-65) and the results are also in good agreement with the findings of this work.…”
Section: Gc-ms Analysissupporting
confidence: 89%
“…59) and the seed oils were reported to possess an excellent energy substitute properties. The physicochemical results of the biodiesel showed that it can be used in any diesel engine (53). Many studies on the production of biodiesel from vegetable and seed oils were presented (5, 16, 43, 60-65) and the results are also in good agreement with the findings of this work.…”
Section: Gc-ms Analysissupporting
confidence: 89%
“…On the other hand, food shortages may occur due to the use of large amounts of edible oils in producing biodiesel, especially in poor countries. These drawbacks can be overcome by using inedible oils for biodiesel production like Aleurites trisperma , bitter almond, Brucea javanica seeds, Argemone Mexicana, wild mustard ( Brassica Juncea L. ) seed, and tobacco ( Nicotiana tabacum L.) seed ( Arumugam et al, 2017 ; Muthukumaran et al, 2017 ; Jain, 2019 ; Wang et al, 2019 ; Adepoju, 2020 ; Tlili et al, 2020 ). Generally, tobacco, Nicotiana tabacum , which is an annual plant in the Solanaceae family with leaves harvested to manufacture cigarettes, is widespread in China and North and South America, and the leaves are commonly harvested.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches mainly included chemical (acid-base), biological (enzymatic) and mechanical (grinding) pretreatment methods to help increase the bioavailability of usable biomass. These previously employed approaches have some strategic, economic and operational issues such as temperature, pressure, pH, clean up, lower outputs and contamination in the anaerobic digester [5].…”
Section: Introductionmentioning
confidence: 99%